The use of ultrasound for cleaning the surface of stainless steel and nickel-titanium endodontic instruments - Tanomaru, M.; Leonardo, M. R.; Bonifacio, K. C.; Dametto, F. R.; Silva, IAB (Blackwell Science, 2001)
Aim the aim of this study was to evaluate the efficacy of ultrasound in cleaning the surface of stainless steel and Ni-Ti endodontic instruments.Methodology Twenty nickel-titanium instruments (10 Quantec files and 10 Nitiflex) and 20 stainless steel K-files (10 Maillefer-Dentsply and 10 Moyco Union Broach) were removed from their original packages and evaluated using a scanning electron microscope. Scores were given for the presence of residues on the surface or the instruments. The instruments were then cleaned in an ultrasonic bath containing only distilled water or detergent solution for 15 min, and re-evaluated, using scanning electron microscopy.Results Before cleaning, a greater amount of metallic debris was observed on the nickel-titanium Quantec instruments (P < 0.05), when compared to those made of stainless steel. Statistical analysis showed that the use of ultrasound was effective for cleaning the instruments, regardless of the irrigating solution or the instruments type (P < 0.05).Conclusions the use of ultrasound proved to be an efficient method for the removal of metallic particles from the surface of stainless steel and Ni-Ti endodontic instruments.
Keywords: endodontic instruments; Ni-Ti instruments; ultrasound in endodontics